2021
DOI: 10.2196/27603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Phone Text Message Reminders on the Completion and Timely Receipt of Routine Childhood Vaccinations: Superiority Randomized Controlled Trial in Northwest Ethiopia

Abstract: Background Nonattendance at vaccination appointments is a big challenge for health workers as it is difficult to track routine vaccination schedules. In Ethiopia, 3 out of 10 children have incomplete vaccination and the timely receipt of the recommended vaccines is low. Thus, innovative strategies are required to reach the last mile where mobile technology can be effectively utilized to achieve better compliance. Despite this promising technology, little is known about the role of text message–base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…A total of 54,224 parents were recruited as participants in all the studies and numbers ranged from 42 in the study of Niederhauser et al [ 26 ] to 13,000 in the study of Busso et al [ 27 ]. In almost all the studies, participants were reportedly mothers or caregivers of the children [ 7 , 9 , 12 , 13 , 15 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 ]. Two studies reportedly mentioned males as participants, Hofstetter et al [ 39 ] reported a nearly even distribution of participants, male (1051) and females (1003) and Niederhauser et al [ 26 ] reported only one male participant in their study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 54,224 parents were recruited as participants in all the studies and numbers ranged from 42 in the study of Niederhauser et al [ 26 ] to 13,000 in the study of Busso et al [ 27 ]. In almost all the studies, participants were reportedly mothers or caregivers of the children [ 7 , 9 , 12 , 13 , 15 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 ]. Two studies reportedly mentioned males as participants, Hofstetter et al [ 39 ] reported a nearly even distribution of participants, male (1051) and females (1003) and Niederhauser et al [ 26 ] reported only one male participant in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies were included in the review to evaluated parental reminder or recall strategies for improved immunisation. Out of the 24 studies, 19 [ 9 , 13 , 15 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] provided sufficient information and were therefore included for meta-analysis. The 19 studies assess five different parental reminder/recall strategies on two major immunisation outcomes: coverage and timeliness of immunisation among children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health information technology tools, including health care mobile apps for use on a personal smartphone or desktop computer, have been demonstrated to be a sustainable strategy for facilitating patient provider communication, disseminating high-quality evidence-based information to end users on a global scale, increasing adherence to medical regimens and tracking when medical interventions are due, and improving outcomes in chronic illnesses [8][9][10][11][12]. mHealth (mobile health) apps have been successfully created and implemented to facilitate immunization delivery [13][14][15][16][17][18][19][20]. However, mHealth apps have never been utilized to improve immunization rates in high-risk populations (such as children awaiting transplant) who require a tailored vaccine schedule (such as the accelerated vaccine schedule) and comanagement by multiple providers (including the primary care physician and transplant team) who in turn may operate on different electronic medical records (EMRs).…”
Section: Introductionmentioning
confidence: 99%